Virtual reality assisted fluorescence microscopy data visualisation and analysis for improved understanding of molecular structures implicated in neurodegenerative diseases - Theart, Rensu P. (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.